2014
DOI: 10.1017/s1368980014002432
|View full text |Cite
|
Sign up to set email alerts
|

Low dietary intake of magnesium is associated with increased externalising behaviours in adolescents

Abstract: Objective: Adequate Zn and Mg intakes may be beneficial for the prevention and treatment of mental health problems, such as depression, anxiety and attentiondeficit hyperactivity disorder. We aimed to investigate the prospective association between dietary intakes of Zn and Mg and internalising and externalising behaviour problems in a population-based cohort of adolescents. Design: Prospective analysis (general linear mixed models) of dietary intakes of Zn and Mg assessed using a validated FFQ and mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Magnesium supplementation in women with PCOS improved emotional and mental aspects of quality of life. Previous studies showed that low magnesium intake was significantly associated with externalizing behaviors [59], whilst another study found an inverse relationship between dietary magnesium intake and incidence of depression [17]. A review study asserted favorable effects of magnesium supplementation on different types of mental disorder including depressive symptoms, anxiety disorders, attention deficit hyperactivity disorder, autism, obsessivecompulsive disorder, and eating disorders [60].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium supplementation in women with PCOS improved emotional and mental aspects of quality of life. Previous studies showed that low magnesium intake was significantly associated with externalizing behaviors [59], whilst another study found an inverse relationship between dietary magnesium intake and incidence of depression [17]. A review study asserted favorable effects of magnesium supplementation on different types of mental disorder including depressive symptoms, anxiety disorders, attention deficit hyperactivity disorder, autism, obsessivecompulsive disorder, and eating disorders [60].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Australia showed a statistically significant association between higher dietary Mg intake and reduced externalizing behavior problems in adolescents [ 49 ]. Since a lower intake of magnesium in ADHD has been reported [ 50 , 51 ] many supplementation studies have been carried out to correct the magnesium homeostasis.…”
Section: Magnesium (Mg)mentioning
confidence: 99%
“…Nearly all studies found lower daily intake of zinc in ADHD children [ 49 , 50 , 55 , 56 , 125 ]. In only one publication zinc intake was not different in ADHD compared to healthy controls [ 28 ].…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Recent meta-analyses have shown clear links between poor diet and cognitive impairment, dementia, Alzheimer's disease, and especially depression (Psaltopoulou et al, 2013;Lai et al, 2014;Jacka et al, 2017). Adults with mood disorders have been shown to increase functioning when consuming diets high in micronutrients (Davison and Kaplan, 2012;Jacka et al, 2017), especially Mg (Black et al, 2015;Tarleton and Littenberg, 2015). It is fair to assume that decreased nutritional quality, such as increased C:Mg in staple crops, is likely to have pronounced effects on mental health.…”
Section: Dietary Stoichiometry and Mental Healthmentioning
confidence: 99%